Signposts Signify Troubled Waters Ahead for Taiwan-U.S. Relations - Gipson, Ronnie R. (American Journal of Trade and Policy, 2022)
The issue of Taiwan’s independence and protection is reminiscent of Poland’s position in the late 1930s, facing unbridled aggression from Nazi Germany. Great Britain and France promised to declare war if Germany attacked Poland. However, after Germany attacked Poland on September 1, 1939, neither Great Britain nor France deployed troops to Polish soil to rebuff the attack and restore Poland’s sovereignty. The promise of assistance was an empty promise that the Polish people paid dearly. History teaches us that an ambiguous assistance policy will not stop naked aggression. A firmer stance and a more transparent approach are warranted from a diplomatic standpoint. This article is an essay that sets forth and supports the premise that the United States should clarify and strengthen its position of support for Taiwanese independence. Preprint (November 18, 2021). Available at SSRN: https://papers.ssrn.com/sol3/papers.cfm?abstract_id=3939120